An In Vitro Comparison of Antimicrobial Effect of Nanosil and ChlorhexidineMouthrinses - Vahid Esfahanian; Ferida Mohamadi; Shahram Amini (Islamic Dental Association of Iran, 2012)
Background and Aim: Regarding chemical methods of plaque control, use mouthrinses are more frequent than other methods. The objective of this research is making a comparison between the antibacterial effect of Nanosil and chlorhexidine mouthwashes .   Materials and Methods: In this experimental study samples were taken from supragingival and subgingival plaques of 15 patients and transferred to aerobic and anaerobic liquid culture environments. The number of the bacteria in both aerobic and anaerobic liquid environments were determined by spectrophotometer. Then, the samples were transferred from the liquid culture environment to the considered solid culture environment as a mixture of nanosil and chlorhexidine mouthwashes and placebo and the numbers of the growth colonies in the solid culture environment were counted in each group and compared with each other by t test .   Results: In both aerobic and anaerobic conditions, the number of the growth colonies, was depicted in ascending order the groups of chlorhexidine, nanosil, and placebo. Concerning chlorhexidine, there was no significant difference between the growth colonies in the two aerobic and anaerobic environments indicating the absolute antibacterial effect of this mouthwash.   Nanosil mouthwash had a significant statistical superiority in comparison with the placebo in both aerobic and anaerobic environments. Nanosil had a significant effect on anaerobic environment, meanwhile, the placebo indicated a superior effect in anaerobic environment .   Conclusion : Nanosil mouthwash can be applied as an effective antibacterial substance especially in an anaerobic environment, though chlorhexidine as a standard mouthwash has still the strongest effect in this field .